The Role of The Headmaster As An Innovator In The Vocational High School Field of Business And Management Padang City - Nellitawati Nellitawati (Jurnal Konseling dan Pendidikan, 2018)
The goals of this research are to see information about the headmaster's role as an innovator. The population is 127 teachers, and the sample is 83 people that taken by proportional random sampling. The instrument of this research is a question with Likert scale models that tested for validity and reliability. Data analyzed using mean score and performance level. The result from this research are the headmaster’s role of an innovator in  The Vocational High School Field of Business and Management Padang City stay in good enough category.